Truth, Discussion, and Free Speech in On Liberty II. Issue 2 (June 2021) - Macleod, Christopher
Abstract: In this article, I offer a reading of On Liberty II which focuses on the structural features of the argument that Mill presents. Mill's argument, I suggest, is grounded on an appeal to the value of truth, and is divided into three sub-arguments, treating true, false and partially true opinion respectively. In section 1, I consider what constraints the teleological orientation of Mill's argument places on the case he makes, before examining in section 2 what the division of Mill's argument into three exhaustive sub-arguments tells us about the nature of 'discussion' as Mill uses the term. I go on, in section 3, to suggest that although On Liberty II does not offer a defence of free speech in the broad sense in which the term is often now used, we should be optimistic about the chances of finding such a defence in On Liberty III.